2011
DOI: 10.4049/jimmunol.1002788
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles (Ectosomes) Shed by Stored Human Platelets Downregulate Macrophages and Modify the Development of Dendritic Cells

Abstract: Microparticles (MP) shed by platelets (PLT) during storage have procoagulant activities, but little is known about their properties to modify inflammation or immunity. In this study, we studied the capacity of MP present in PLT concentrates to alter the function of macrophages and dendritic cells (DC). The size of the purified MP was between 100 and 1000 nm, and they expressed phosphatidylserine; surface proteins of PLT (CD61, CD36, CD47), including complement inhibitors (CD55, CD59), but not CD63; and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
158
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(174 citation statements)
references
References 45 publications
8
158
2
1
Order By: Relevance
“…It has previously been shown that, in platelet–PBMC coculture, activated platelets slightly but nonsignificantly reduced monocyte HLA‐DR expression in response to LPS 19. Similarly, platelet microparticles can reduce HLA‐DP, DQ and DR expression on monocyte‐derived dendritic cells, with the authors suggesting that monocytes that come into contact with platelet microparticles may be less likely to develop into fully pro‐inflammatory dendritic cells 15. In our study, it is unclear why an effect of platelets was observed with low‐dose LPS, but not observed under any other condition tested.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has previously been shown that, in platelet–PBMC coculture, activated platelets slightly but nonsignificantly reduced monocyte HLA‐DR expression in response to LPS 19. Similarly, platelet microparticles can reduce HLA‐DP, DQ and DR expression on monocyte‐derived dendritic cells, with the authors suggesting that monocytes that come into contact with platelet microparticles may be less likely to develop into fully pro‐inflammatory dendritic cells 15. In our study, it is unclear why an effect of platelets was observed with low‐dose LPS, but not observed under any other condition tested.…”
Section: Discussionmentioning
confidence: 92%
“…Platelets have been shown to dampen leucocyte activation and pro‐inflammatory cytokine production in both mouse models of sepsis14 and in vitro cell models of infection,15, 16 and this platelet effect is associated with host defence and survival in sepsis 17, 18. The regulatory effect of platelets has largely been characterised in peripheral blood mononuclear cells (PBMCs) in vitro exposed to lipopolysaccharide (LPS; a TLR4 agonist), or in mouse models of sepsis 14, 17, 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the data on PMN-derived EVs (called in these studies ectosomes) come from the laboratory of Dr. Schifferli [26,[34][35][36]39,40,45,[93][94][95][96]. They characterized the size and surface properties of EVs released upon fMLP-stimulation and came to the conclusion that both the in vitro and the in vivo generated EVs are right-side out [39,45].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 99%
“…However, the specificity of PMN-derived EVs in this process remains to be determined, as EVs produced by stored erythrocytes [94] and platelets [93] have also been reported to down-regulate macrophages and dendritic cells.…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 99%
“…11 The composition and pathogenic roles of MP have been extensively studied in various diseases, such as ischemia, diabetes and atherosclerosis, revealing complex pathogenic roles in modulating nitric oxide and prostacyclin production, stimulating cytokine release, inducing tissue factor expression, as well as monocyte chemotaxis and adherence to the endothelium. [12][13][14][15][16][17][18] Recent studies on the mechanisms of redox regulation of RBC membrane stability 19,20 indicate that oxidative stress induces a phosphorylative response that specifically involves two tyrosine residues located in the cytoplasmic domain of band 3. 20 Band 3 is the most abundant RBC membrane protein, and represents one of the major components of the junctional complexes that connect the lipid bilayer to the cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%